Angiotensin 1 peptide-conjugated CdSe/ZnS quantum dots for cardiac-specific hydrogen sulfide targeted therapy in myocardial ischemia-reperfusion injury - Wang, Qing; Xue, Xiaofei; Wang, Pei; Yu, Yue; Wang, Jun; Jiang, Qixia; Xiao, Jian (Frontiers in Pharmacology, 2024)
Introduction Myocardial ischemia/reperfusion (I/R) injury remains a major obstacle in cardiovascular therapies. Hydrogen sulfide (H2S) shows promise for mitigating I/R injury, but conventional delivery methods, such as NaHS injections or adenovirus-mediated CSE gene therapy, face low efficiency and systemic side effects. This study explores the use of angiotensin 1 (AT1) peptide-conjugated CdSe/ZnS quantum dots (QDs) for targeted delivery of cystathionine-γ-lyase (CSE) plasmids to the myocardium, aiming to boost local H2S production and minimize I/R injury. Methods CdSe/ZnS QDs were conjugated with AT1 peptides to create a nanocarrier system capable of delivering the CSE plasmid specifically to the myocardium. In vivo fluorescence imaging confirmed heart-specific accumulation. Myocardial infarct size, cardiac function, cell death, and oxidative stress were evaluated. Endoplasmic reticulum stress and mitophagy markers, including CHOP/GRP78/eIF2α, were analyzed, and the CHOP gene's role was further assessed using an adenovirus vector. Results The AT1-conjugated nanocarriers significantly increased CSE expression in the myocardium, as confirmed by fluorescence imaging, without affecting other organs. This localized delivery reduced myocardial infarct size, improved cardiac function, and decreased oxidative stress and cell death. Importantly, a reduction in endoplasmic reticulum stress and mitophagy markers was observed, suggesting that cardioprotection was mediated via the CHOP/GRP78/eIF2α signaling pathway. Reintroduction of CHOP using an adenovirus vector reversed these protective effects, confirming the pathway's involvement. Discussion This study demonstrates that AT1 peptide-conjugated QDs can effectively deliver CSE plasmids to the heart, providing significant protection against I/R injury through enhanced localized H2S production. This approach offers a promising, targeted, and side-effect-free therapy for myocardial I/R injury, with potential for clinical translation.